Work inspections as a control mechanism for mitigating work accidents in Europe - Lafuente, Esteban (2020)
This study analyzes the relationship between work inspections—which are a relevant control mechanism of countries’ safety function—and the rate of work accidents in Europe. The empirical application is based on fixed-effects regression models on a sample of 24 European countries for the period 2008-2015. The results confirm the pro-cyclical relationship between the rate of work accidents and economic activity (GDP) among the sampled countries. Additionally, the findings reveal that work inspections are an important control mechanism that significantly contributes to alleviate the rate of work accidents. In line with increased awareness of occupational health and safety (OHS) as a relevant dimension of territories’ productive structures, policy implications and future research avenues are discussed.